Instructional Supervision, Feedback Quality, and Teacher Perceptions: A Multi-Method Synthesis - Bacharo, Richie (JPAIR Institutional Research, 2026)
Instructional supervision and feedback are pivotal mechanisms for enhancing teacher competence and elevating instructional quality. This paper synthesizes peer-reviewed research to explain how supervision, feedback quality, and teacher perceptions interact within standards-aligned observation frameworks. Anchored on developmental supervision theory, social constructivism, and policy-practice alignment, the synthesis integrates quantitative findings and qualitative insights to illustrate why supervision succeeds when schools enact calibrated observation, goal-referenced, dialogic post-observation conferences, and timely, specific, actionable feedback. Across recent scholarship (2020-2025), supervision tends to produce larger competence gains when enacted as developmental coaching rather than compliance monitoring, and when feedback is practice-proximal; conversely, generic or delayed feedback and routine inspection often yield weak or null effects. The review identifies recurring implementation constraints (e.g., workload, time, supervisory expertise), delineates moderated-mediation pathways wherein feedback quality and teacher perceptions both mediate and amplify supervision’s impact on competence, and offers actionable recommendations for codifying feedback standards, investing in observer calibration, embedding collaborative reflection, and resourcing supervision for follow-up. Methodologically, the synthesis adopts a convergent mixed methods orientation, integrating quantitative moderated mediation analyses with qualitative insights from post observation conferences and feedback artifacts to illuminate mechanisms of impact. The manuscript contributes a publishable framework that shifts supervision from bureaucratic ritual to an engine of professional growth, and it outlines research directions for rigorous longitudinal and experimental designs and standardized measures of feedback quality and developmental perceptions.